The Use of Linguistic Landscape as a Medium for English Language Learning at Al-Ammar Science High School for Qur'an Memorization - Nurmala, Dewi; Ningsih, Ayu Melati; Wardana, Muhammad Kiki; Siregar, Riska Safitri; Syafrida, Nazwa (Westscience Press, 2025)
This article is the result of the community service activity of a team of lecturers and students of Universitas Muslim Nusantara Al-Washliyah from the English literature study program. The purpose of this community service is to share knowledge of the use of linguistic landscape as a medium for English language. Landscape linguistics is a study of language use in public spaces. The program was designed to enhance students’ exposure to English through the strategic use of signs, posters, labels, and educational displays placed in the school environment. The implementation of this program demonstrated that the linguistic landscape could function as an effective, low-cost, and sustainable learning medium. Students showed increased interest and familiarity with English vocabulary and expressions encountered in their daily school activities. Furthermore, the program proved that English language learning can be harmoniously integrated into a religious-based educational setting without disrupting the school’s focus on Qur'an memorization. Through this activity, it is hoped that it will increase the knowledge and insight of the participant.